Optimizing Waste Management for Circular Economy and Low-Carbon Development: A Case Study of Depok City, Indonesia - Tri Utomo, Emod; Ekayani, Meti; Abidin, Zaenal (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
In Depok, Indonesia, rapid urbanization and economic growth have significantly increased waste production, exposing inefficiencies in existing management systems that contribute to environmental, health, and socio-economic problems, including pollution and rising greenhouse gas (GHG) emissions. This study evaluates the investment and operational requirements for optimal waste management, estimates potential GHG reductions compared to a Business as Usual (BAU) baseline in 2030, and examines policy implications that support a circular economy and low-carbon development. A mixed-method approach was employed by integrating field surveys, stakeholder interviews, and secondary data from local government and environmental agencies. Emissions were calculated for 2025 to 2030 using Intergovernmental Panel on Climate Change (IPCC) 2006 Tier 1 methods, while descriptive analysis was applied to interpret institutional and policy readiness. The results demonstrate that an optimized scenario, which emphasizes decentralized composting, recycling infrastructure, and improved governance, could achieve a 65% reduction in GHG emissions by 2030 relative to the BAU baseline. Beyond quantifying emissions, the novelty of this study lies in integrating financial, environmental, and governance dimensions within a city-level framework, which remains underexplored in Indonesian and Southeast Asian waste management research. Strategic recommendations include upgrading community-based facilities, implementing fair waste tariffs consistent with the polluter pays principle, and fostering greater citizen participation. By linking emission mitigation with financial feasibility and institutional mechanisms, this study highlights how secondary cities such as Depok can serve as models for advancing circular economy and low-carbon urban transitions in Indonesia.